Combined longitudinal-torsional vibration of sandwiched piezoelectric ultrasonic transducers - Demir, Bülent Güven. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
In this thesis, combined longitudinal-torsional vibration of ultrasonic transducer using impedance matching method is studied. In combined vibration, two modes must resonate in the same frequency. Impedance matching method is applied the modes to find spatial solutions of the parts. Spatial solutions of horns are derived for each mode. Dimensional parameters of the transducer are studied, and change of resonance frequencies is presented to give the idea how to synchronize the modes of the transducer. Changing the dimensions of the transducer, resonance frequencies of two modes are equalized. This shows that synchronization of two modes is an adjustment problem. For illustration of the application of theory, sample transducers are designed.
Keywords: Piezoelectric transducers.; Ultrasonic welding.